Analisis Kesalahan Berbahasa Bidang Fonologi Pidato Terakhir Presiden Joko Widodo pada HUT ke-79 TNI Tahun 2024 di Monas - Okky Kharisma (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The purpose of this study was to determine the analysis of language errors in the phonology of Joko Widodo's last speech at the 79th Anniversary of the TNI in 2024 at Monas. This research was conducted by means of a literature study. The data source for this study was a document, namely a video. The research method used was descriptive qualitative. The data collection technique was to observe and take notes, in addition to listening carefully to the acquisition of data sources. In the video, there were 17 errors in the phonology level of phoneme deletion and 6 phoneme changes.